2022
DOI: 10.3389/fcell.2022.951816
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filaments: Integration of cell mechanical properties during migration

Abstract: Cell migration is a vital and dynamic process required for the development of multicellular organisms and for immune system responses, tissue renewal and wound healing in adults. It also contributes to a variety of human diseases such as cancers, autoimmune diseases, chronic inflammation and fibrosis. The cytoskeleton, which includes actin microfilaments, microtubules, and intermediate filaments (IFs), is responsible for the maintenance of animal cell shape and structural integrity. Each cytoskeletal network c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…This discovery broadens the known genetic spectrum of KRT4 mutations associated with WSN. The primary roles of KRT include maintaining cellular integrity, facilitating intercellular adhesion, and participating in intracellular signal transmission, material transport, and cell differentiation [ 13 , 14 ]. Altered expression patterns of KRT during and post-malignant transformation have been reported to influence various signaling pathways implicated in tumor progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This discovery broadens the known genetic spectrum of KRT4 mutations associated with WSN. The primary roles of KRT include maintaining cellular integrity, facilitating intercellular adhesion, and participating in intracellular signal transmission, material transport, and cell differentiation [ 13 , 14 ]. Altered expression patterns of KRT during and post-malignant transformation have been reported to influence various signaling pathways implicated in tumor progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent studies have demonstrated that vimentin, which contributes to cells resilience against mechanical stress [ 54 ], generates with actin and microtubules the forces required for cell adhesion. More specifically, vimentin regulates stress generation by adherent cells through an interplay with actin stress fibers [ 55 ]. We can speculate that alteration of the mechanical forces within the glomerulus in vivo may lead to cytoskeleton alterations and the detachment of renal progenitors from the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate filaments, including nuclear lamins and vimentins, are connected to other cytoskeletal elements through the LINC complex and binding proteins like plectin. Therefore, intermediate filaments may also play a role in mechanotransduction, but their molecular mechanism is less explored compared to other cytoskeletal components [248].…”
Section: Cell and Tissue Mechanics In Normal And Aberrant Physiologymentioning
confidence: 99%